Factors Associated with Stiffness Following Pediatric and Adolescent ACL Reconstruction: Early Results from Score: A Multi-Center Quality Improvement Registry. Issue 5 (31st May 2022) - Cooper, Savannah; Adsit, Lizzie R.; Schmitz, Matthew; Ganley, Theodore; Ellington, Matthew; Rhodes, Jason; Frank, Jeremy; Mansour, Alfred; Saper, Michael; Parikh, Shital; Mayer, Stephanie; Wilson, Philip; et al.
Background: Anterior Cruciate Ligament reconstruction (ACLr) is commonly performed in pediatric and adolescent patients. The most common early complication associated with ACLr is stiffness, including motion loss and arthrofibrosis. There is minimal literature regarding risk factors for stiffness following ACLr in this age group. Hypothesis/Purpose: To evaluate the incidence and risk factors associated with stiffness following ACLr using a multi-center quality improvement registry. Methods: A multi-center quality improvement registry (16 institutions, 26 surgeons) monitoring the safety of ACLr was reviewed. Audit processes using CPT codes were designed to insure that all consecutive cases were prospectively entered on patients <19 years old into a HIPAA-compliant electronic platform. Stiffness was defined as motion loss that prompted any deviation from the normal post-operative course (Clavien Dindo grade II or greater), including additional clinical or physical therapy (PT) visits, serial/dynamic splinting, or secondary surgery for stiffness (Clavien Dindo grade III). Each case of stiffness and associated complication form was secondarily reviewed to insure consistency of identification and grading. Demographic and peri-operative data were reviewed. Chi-Square or Fisher's exact tests were used for categorical comparisons and a Kruskal-Wallis test for continuous comparisons. Results: 2, 839 ACLr cases (mean age 15.1, 6-19; female 46.9%) were identified, with stiffness reported in 4.2% of patients (including isolated flexion or extension and combined stiffness) and secondary surgery for stiffness (manipulation under anesthesia and/or lysis of adhesions) performed in 1.1% of patients. Loss of extension occurred in 3.8% of patients (59.3% females), while loss of flexion occurred in 3.1% of patients (49.4% females). Overall stiffness occurred with longer tourniquet times (93.0 min vs. 78.8 min, p<0.001) when used. Anterior displacement of medial or lateral meniscus tear were associated with nearly twice the incidence of extension loss (7.1%) and three times the incidence of surgery for stiffness (3.7%). Conclusion: Post-operative stiffness following ACLr is rare but may be associated with certain demographic and perioperative factors, such as female sex, prolonged tourniquet time, and certain concomitant injuries such as anteriorly displaced meniscus tears. The degree to which altered practices and/or additional monitoring/vigilance in the setting of such factors warrants additional study.